CERN turns 50. - Sweet, W.
On the 29th September, the particle physics laboratory in Geneva known as CERN-the European Organization for Nuclear Research-celebrated its 50th birthday. In the past half century, CERN has emerged as the world's preeminent laboratory for the study of elementary particles, and it serves today as a focal point of European pride.
Keywords: CERN; European Organization for Nuclear Research; World Wide Web; All electronic detector; Grid computing; Stochastic cooling; Superconducting magnets